Transforming Health through e-Payments in India - Isern, Jennifer (World Bank, Washington, DC, 2017)
The World Bank Group (WBG), in collaboration with the Government of Bihar, is implementing a government-to-person (G2P) health payments project with co-funding from the Bill and Melinda Gates Foundation (BMGF). The timeliness and integrity of these monetary incentives are key to their effectiveness. In late 2009, WBG began discussions with the State Health Society of Bihar (SHSB) and BMGF about delays and inefficiencies related to conditional incentive payments to health program beneficiaries and health workers. On the basis of those initial discussions, WBG conducted a diagnostic with SHSB on health payments in Bihar in 2010-11. WBG found that health programs in Bihar experienced significant delays (ranging from two months to two years) in making incentive payments and that health officials spent nearly 30 percent of their time administering payments instead of providing health care services. To address those challenges, WBG recommended that SHSB modernize its health payment system by: (a) automating the calculation, verification, and recording of payments; (b) enabling centralized payment processing; and (c) making payments using electronic funds transfers directly into beneficiary bank accounts.